A current review of the use of mobile technology to enhance learning and communication among children with development disabilities. - Anuar Mohd Yusof; H. Song (2010)
An autistic person is said to have impairments in social interaction, emotional development, communication disorder as well bizarre behaviors that severely affects their relationship with their families and others around them. It also reported that 50% of individual diagnosed with autism do not speak but are highly visual-oriented with the presence of strong visual-spatial skills. Autistic persons are drawn to and respond well to visual representation which includes written words as well. In UK, USA and other European countries, there is a wide array of intervention techniques which take advantage of these visual inclinations and strength to improve these impairments. Among the intervention techniques, Augmentative and Alternative Communication (AAC) systems had received much attention and are used very often by professionals and therapist to teach social and communication skills to children with autism. The AAC systems and techniques are commendable with a plethora of research evidence citing its usefulness and effectiveness and had since improved many lives of autistic persons. However, each of these techniques has its limitations such as mobility, expensive cost as well as practicality. Some researcher has addressed some of these limitations by marrying these techniques with emerging technologies such as mobile devices. With the flexibility of multimedia content, easy portability and relatively cheaper cost, plus easy content creation capabilities, there is immense potential to utilize mobile devices to teach autistic persons with specialized and individualized content. It serves as an AAC in the pocket and had since gained popularity because of its flexible multimedia content and storage, portability, mobility and affordability. The touch screen interface makes it appealing and simple to use as well. This paper, therefore provides a current review of research literature and case studies related to the use of mobile technology as educational intervention to enhance learning and communication among children with developmental disabilities particularly those located in the autistic spectrum.